2008
DOI: 10.1002/clc.20264
|View full text |Cite
|
Sign up to set email alerts
|

Is Myocardial Performance Index an Independent Echocardiographic Marker of Death in Children with Idiopathic Dilated Cardiomyopathy?

Abstract: Background: Myocardial performance index (MPI) was reported as a parameter of ventricular systolic and diastolic function, as well as a useful tool to predict the outcome in patients with ventricular dysfunction. Hypothesis: To compare MPI with classical echocardiographic parameters as an independent marker of death in children with idiopathic dilated cardiomyopathy (IDCM). Methods: Fifty-five children (13 deaths) underwent 104 echocardiograms from January 1996 to May 2005. Right ventricle (RV) MPI and left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…It is an independent predictor of worsening outcomes in adult and pediatric patients with DCM[10-12]. In a study of 161 healthy children, the Doppler Tei index decreased until 3 years of age, after which it did not change[2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an independent predictor of worsening outcomes in adult and pediatric patients with DCM[10-12]. In a study of 161 healthy children, the Doppler Tei index decreased until 3 years of age, after which it did not change[2].…”
Section: Discussionmentioning
confidence: 99%
“…Its original description utilized Doppler mitral valve inflow and aortic outflow velocities[9]. It has been reported as an indicator of adverse outcomes in pediatric and adult patients with dilated cardiomyopathy (DCM)[10-12]. With TDI, the Tei index can be determined from myocardial velocities despite limited 2-dimensional acoustic windows and may be more accurate in pediatric patients as it is less altered by heart rate variability[13].…”
Section: Introductionmentioning
confidence: 99%
“…MPI obtained from PWD method has been described as a noninvasive index reflecting combined LV function 10,22 . Several studies have shown the utility of PWD‐MPI as a reliable predictor of outcome in a variety of diseases 23,24 . Such results suggest that the early diagnosis of initial phase of heart failure using the PWD‐MPI could improve cardiovascular prognosis; this is becoming more important nowadays because of increased life span of children after renal transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The utility of MPI has also been demonstrated in children with idiopathic dilated cardiomyopathy, where it was shown to be an independent, predictive measure of mortality (Azevedo et al. ). In mdx mice, an animal model of DMD, MPI is significantly increased by 12 months of age compared to WT mice, indicating left ventricular dysfunction (Adamo et al.…”
Section: Introductionmentioning
confidence: 99%